1983
DOI: 10.1177/00220345830620100701
|View full text |Cite
|
Sign up to set email alerts
|

Grooved Titanium Surfaces Orient Growth and Migration of Cells from Human Gingival Explants

Abstract: A silicon mask-etching technique was used to prepare grooved surfaces that control the direction of outgrowths of human gingival explants. The method used to produce the grooves is excellent in terms of both the uniformity of the grooves and the control with which surfaces of the desired specifications can be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(90 citation statements)
references
References 8 publications
2
85
0
2
Order By: Relevance
“…However, the effect of cylindrical topography on cell nuclei alignment disappeared when fiber diameter was bigger than 200 μm. Brunette et al (Brunette et al, 1983) studied outgrowth of human gingival explants on a titanium surface etched with trapezoid shape grooves (groove upper width 130 μm and lower width 60 μm, ridge width 10 μm). The direction of outgrowth was strongly guided by the grooves.…”
Section: Tissue Subunits (Submillimeter) Scale Topographymentioning
confidence: 99%
“…However, the effect of cylindrical topography on cell nuclei alignment disappeared when fiber diameter was bigger than 200 μm. Brunette et al (Brunette et al, 1983) studied outgrowth of human gingival explants on a titanium surface etched with trapezoid shape grooves (groove upper width 130 μm and lower width 60 μm, ridge width 10 μm). The direction of outgrowth was strongly guided by the grooves.…”
Section: Tissue Subunits (Submillimeter) Scale Topographymentioning
confidence: 99%
“…72 " 74 Thus, it appears that the direction of cellular outgrowth from a source (e.g., tissue explants) can be guided by the topology of the substratum and this has been demonstrated with grooved titanium surfaces. 73 Preliminary studies using percutaneous implants have shown that grooving the surface can decrease the length and rate of epithelial migration. 7375 Although the research in this area is revealing important information, very little is known about the effects of changing surface topography of substrata on the proliferation and matrix synthetic profiles of cells.…”
Section: Regeneration Of Connective Tissue Attachment To Previousmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Although various, often ingenious methods have been used to produce different topographies for studies of cell behaviors, the introduction of substrata produced by micromachining enabled a more precise control of substrata geometry to be achieved. 8 Micromachined substrata have now been used in diverse studies of cell and cytoskeletal behavior in vitro 2,4,5,9 and as implant surfaces in vivo. 10,11 A consistent finding is that grooved micromachined substrata alter cell shape and cytoskeletal organization.…”
Section: Introductionmentioning
confidence: 99%